“SOMETHING OLD, SOMETHING NEW” – ASPECTS OF PERSONALITY RIGHTS IN THE UNITED STATES AND SOUTH AFRICA - Karabo Mangope; Wim Alberts (Obiter, 2022)
Advances in technology have made it possible for the least talented person to become an Internet sensation. This has created challenges related to personality or image rights, data protection, privacy, and the right to be forgotten. The position in the United States of America is dealt with first. Individuals can rely on either federal law or state law. Section 43(a) of the Lanham Act prohibits conduct that causes confusion or false representations or deception. The right to publicity is very prominent. The author Prosser divided the right to privacy by reference to four categories of tort: the intrusion of physical solitude; public disclosure of private facts; representations in a false light; and the appropriation of a person’s name and appearance. Richards and Solove believe that the right to publicity is often combined with an individual’s appearance or name. The difference between appropriation and the right to publicity is that the former is traditionally focused on the damage to a person’s right to privacy, while the latter focuses on the person’s right to make money from their image. In South Africa, Cornelius is of the opinion that the approach here is more advanced than in other countries as the right to dignity is protected by the right to identity. Exclusions from liability in America would include newsworthy information and parody. In South Africa, the exclusions are press privilege and parody. The legal position of social media service providers in the United States is such that a high degree of immunity is provided to networks by the Communications Decency Act. Section 230 of the Act was aimed at promoting the free exchange of information and ideas over the Internet and at the control of offensive material. The right to be forgotten occurs in both systems.